Automatic system for wine qualification through Neural Networks - Rivera Demanuel, Diego Richard (2022)
Treatment of data for the qualification of wines, this report details the process followed, where the Python programming language was used, for the analysis of the data of the dataset, the Google Colab server was used to execute the algorithms in the cloud since the team considered that the speed of data analysis in Google Collab is faster. Neural networks have the ability to learn and perform tasks based on an initial training called adaptive learning and are also fault-tolerant.